OP0235 Pet high affinity translocator protein ligands as a novel modality for macrophage targeting in arthritis. (23rd January 2014) - Gent, Y.; Weijers, K.; Molthoff, C.; Windhorst, A.; de Greeuw, I.; Al, M.; Bergstra, R.; Verlaan, M.; Kassiou, M.; Lammertsma, A.; Jansen, G.; van der Laken, C.
Abstract : Background: Activated macrophages infiltrate synovial tissue in early stages of rheumatoid arthritis (RA). Therefore, macrophage targeting is attractive for early diagnostics of RA. The expression of translocator protein (TSPO) on (activated) macrophages has been successfully exploited as a target for noninvasive PET imaging with [ 11 C]-PK11195 in RA patients. However, considerable background activity with this tracer [1] warranted further improvement, which has led to the development of a new generation of TSPO tracers, including DPA-713 and DPA-714, with potentially lower levels of non-specific binding. Objectives: To compare in vitro binding characteristics as well as in vivo PET imaging of macrophages in an antigen-induced rat arthritis model of PET tracers [ 11 C]-DPA-713 and [ 18 F]-DPA-714 with [ 11 C]-PK11195. Methods: Human monocytic-macrophage THP1 cells were used in ligand binding studies with [ 3 H]-DPA-713 as well as competitive binding studies with [ 3 H]-DPA-713 and unlabeled PK11195, DPA-713 or DPA-714. Wistar rats were immunized twice with methylated Bovine Serum Albumin (mBSA), emulsified with Freund's adjuvant and custom Botella Pertussis antigen. Arthritis was induced with an intra-articular injection of mBSA in the right knee (day 21) followed on day 28 by PET scanning after injection of 20 MBq [ 11 C]-DPA-713 (n=7), 20 MBq [ 18 F]-DPA-714 (n=6), 20 MBq [ 11 C]-PK11195 (n=4) and assessment of ex vivo biodistribution after 1 hour. Extracted knee joints were processed for immunohistochemistry (HE and anti-ED-1 as rat macrophage marker). Results: Both DPA-713 and DPA-714 displayed markedly enhanced TSPO binding to THP-1 cells compared to PK11195 (relative binding affinity; DPA-714: DPA-713: PK11195 =40:5:1). PET images of [ 11 C]-DPA-713 and [ 18 F]-DPA-714 in rats demonstrated clear visualization of arthritis. Ex vivo biodistribution showed higher absolute uptake in the arthritic joint with both DPA tracers compared to [ 11 C]-PK11195 with the highest uptake observed for [ 11 C]-DPA-713 (0.7±0.2 (SD) %ID/g). Since tracer uptake in bone marrow most likely accounted for most of the background activity, arthritic joint-to-bone marrow ratios (±SD) were calculated for [ 11 C]-DPA-713, [ 18 F]-DPA-714 and [ 11 C]-PK11195; 1.99±0.26, 1.49±0.42 and 1.35±0.14, respectively. Enhanced tracer uptake due to presence of macrophage-like cells was also revealed in spleen, liver, intestinal organs and lymph nodes. Immunohistochemistry of dissected arthritic knees showed an abundant influx of macrophages in synovium, resembling synovitis in RA patients. Conclusions: Both DPA-713 and DPA-714 revealed higher in vitro binding affinity to TSPO compared to PK11195. Beyond this, novel PET tracers showed promising in vivo imaging of arthritis by targeting TSPO on macrophages in a rat model. In future studies, PET imaging of arthritis with these tracers will be further explored in RA patients. References: C.J. van der Laken et al, Arthritis Rheum (2008); 58: 3350-3355 Disclosure of Interest: None Declared